Association between unrealistic comparative optimism and self‐management in individuals with type 2 diabetes: Results from a cross‐sectional, population‐based study. Issue 2 (5th May 2020) - Karl, Florian M.; Holle, Rolf; Schwettmann, Lars; Peters, Annette; Meisinger, Christa; Rückert‐Eheberg, Ina‐Maria; Laxy, Michael
Abstract: Background and aims: Unrealistic comparative optimism (UO), as the erroneous judgement of personal risks to be lower than the risks of others, could help explain differences in diabetes self‐management. The present study tested the hypothesis that individuals with type 2 diabetes who underestimate their comparative heart attack risk, have a lower adherence regarding recommended self‐management. Methods: We used data from individuals with type 2 diabetes participating in the German KORA (Cooperative Health Research in the Region of Augsburg) GEFU 4 (self‐administered health questionnaire 2016) study. UO was estimated by comparing participants' subjective comparative risk for having a heart attack within the next 5‐years (ie, "higher than others, " "average, " "lower than others"), with their objective comparative 10‐year cardiovascular disease risk based on the Framingham equations. We estimated binary logistic and linear regression models to analyze which characteristics were associated with UO and to test the association between UO and participants' self‐management behaviors (ie, regular self‐monitoring of body weight, blood sugar, and blood pressure, regular foot care, keeping a diabetes diary, and having a diet plan), and their sum score, respectively. All models were adjusted for socio‐demographic and disease‐related variables. Results: The studied sample included n = 633 individuals with type 2 diabetes (mean age 70.7 years, 45% women). Smokers and males were more likely to show UO than nonsmokers and females. Furthermore, a higher blood pressure and a higher body mass index were associated with a higher likelihood of UO regarding heart attack risk. However, UO was not significantly associated with patient self‐management. Conclusions: Unfavorable health behavior and risk factors are associated with UO. However, our results suggest that UO with regard to perceived heart attack risk may not be a relevant factor for patient self‐management in those with type 2 diabetes.